2019
DOI: 10.1007/s10579-019-09474-4
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned: on the challenges of migrating a research data repository from a research institution to a university library

Abstract: The transfer of research data management from one institution to another infrastructural partner is all but trivial, but can be required, for instance, when an institution faces reorganisation or closure. In a case study, we describe the migration of all research data, identify the challenges we encountered, and discuss how we addressed them. It shows that the moving of research data management to another institution is a feasible, but potentially costly enterprise. Being able to demonstrate the feasibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This prevents mistakes from compounding and worsening over the course of a migration (Park, 2018). Account for an extensive testing and transition period . Trippel and Zinn (2021) recommend building both human‐level (e.g. manual review and spot checks) and automated quality control tests (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This prevents mistakes from compounding and worsening over the course of a migration (Park, 2018). Account for an extensive testing and transition period . Trippel and Zinn (2021) recommend building both human‐level (e.g. manual review and spot checks) and automated quality control tests (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…We additionally categorized papers according to their focus, and found that while many papers discuss sustainability broadly, few specifically discuss database migration: 17 papers in the corpus were primarily about migration, either in the form of case studies of a particular database migration or research about migration (Allen, 2017; Bruns et al, 2014; Choi, 2020; Davis, 2015; Doty et al, 2015; Dunn et al, 2016; Fabian, 2006; Fallaw et al, 2021; Klump et al, 2015; Matusiak et al, 2017; Murphy, 2003; Pierce, 2019; Shepard, 2013; Thakar & Szalay, 2010; Thomer et al, 2017, 2018; Trippel & Zinn, 2021). Six focused on database maintenance in preparation for migration (Darcovich et al, 2018; Dressler, 2014; Georgieva and Flinchbaugh, 2021; Walsh, 2010; Wu et al, 2016; Wu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Duplication detection is a difficult process, especially in databases with large volumes of data. As proposed by Trippel and Zinn [7], research databases should be collected, evaluated, and inventoried, and these databases should be accessible in a manner that is easy for those in need of the information. Research databases are compiled from various reliable and valid sources to provide quality research information resources.…”
Section: Introductionmentioning
confidence: 99%